Two new species of Caribbiantes, with the redescription of the type species and a review of male genital patterns in Antillean Stenostygninae (Opiliones: Laniatores: Biantidae) - Barroso, Aylin Alegre; Pérez-González, Abel (Zootaxa, 2024)
Caribbiantes cubanus Šilhavý, 1973, type species of genus Caribbiantes Šilhavý, 1973, is redescribed based on abundant material from the type locality, providing new data on its morphological variability and penis morphology. Two new species of Caribbiantes are described, C. obtusus sp. nov. and C. barbai sp. nov., based on additional specimens from central and eastern Cuba, for which we give information on their geographical distribution, intraspecific variability and habitat. A new diagnosis for Caribbiantes and updated geographic distributions of the included species are provided. The sexually dimorphic glandular structures on the metatarsus III of males for all Caribbiantes species are described. Male dimorphism, most evident in the robustness of the chelicerae, is reported for the studied species. The male genitalia patterns of Antillean stenostygnines species are described. The phylogenetic affinity of Antillean stenostygnines with Stenostygnus Simon, 1879, a genus from the north of South America, is discussed based on some morphological traits.